OLED (Organic Light Emitting Diode) display device and circular polarization composite film dry process preparation method thereof
By using the different layer and low -folding coating of the LCD -crystal material in the return light road of the OLED display, the problem of the image heavy shadow and interference color patterns is solved, and a thinner and more efficient optical device is achieved.
Patent Information
- Application Number
- CN202411936630.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The rewinding light path in existing OLED displays has caused image ghosting and interference color patterns due to the interface reflection of the quarter-wave plate and the interlayer reflection between the composite film layers, which affects the viewing experience.
The differences in the bit of the traditional high -molecular membrane material are used to stretch the bits and stretching of the LCD.
The thickness of the retardation film and the thickness of the overall optical device are reduced, the problem of image ghosting is reduced, and the thinness and bendability of the optical device are improved, improving the viewing experience.
Smart Images

Figure CN119360754A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor displays, and in particular to an OLED display device and a circularly polarized composite film dry process preparation method thereof. Background Art
[0002] In a conventional semiconductor display device (such as an OLED display), a return light path is used, wherein the return light path is as shown in the attached Figure 2 As shown: light is emitted from the display screen, and most of it is reflected on the surface of the composite film (solid line). A small part of the light passes through the composite film. The light reflected by the half-reflecting mirror is reflected by the half-transparent mirror for the second time and reaches the surface of the composite film. Among the light reaching the surface of the composite film, most of the light passes through the composite film and reaches the human eye (i.e., the displayed image observed), and a small part is reflected to the display screen, and then the above propagation process is repeated again to reach the human eye (i.e., the observed stray light). Among them, the composite film is a combination of POL (absorption type linear polarizer) + RP (reflection type linear polarizer) + QWP (quarter wave plate). One side of the POL (absorption type linear polarizer) is connected to the glass lens by an adhesive. By converting the output light of the display screen into circularly polarized light, and setting a quarter wave plate on the side of the reflective linear polarizer close to the display screen, the circularly polarized light is converted into linearly polarized light, which can improve the light utilization rate of the entire optical path; but due to the interface reflection on the surface of the quarter wave plate, coupled with the interlayer reflection between the layers in the composite film and the coupling of the film thickness, the image will produce ghosting phenomenon (such as Figure 3 as shown) and interference fringes (as shown Figure 4 This will affect the user's viewing experience. Summary of the invention
[0003] The purpose of the present invention is to solve the deficiencies in the prior art and to provide an OLED display device and a circularly polarized composite film dry process preparation method thereof.
[0004] The object of the present invention is achieved through the following technical solution: an OLED display device, comprising a circular polarizing composite film, wherein the circular polarizing composite film sequentially comprises a low-refractive coating, a phase difference layer, a reflective linear polarizer, an absorbing linear polarizer, and a lens glass; The dry process preparation method of the circularly polarized composite film comprises the following specific steps: Step 1: uniformly coating the photo-alignment solution on the carrier layer to form a photo-alignment layer; Step 2: uniformly coating the liquid crystal solution on the photo-alignment layer and aligning the photo-alignment layer to obtain a phase difference layer, wherein the dry film thickness of the phase difference layer is 0.5-5 microns; and then separating the alignment layer from the phase difference layer; Step 3: coating an adhesive on the phase difference layer, placing a reflective linear polarizer on the phase difference layer and pressing the reflective linear polarizer on the phase difference layer to obtain a reflective linear polarizer-phase difference layer composite structure; Step 4: Using a low-refractive material as a target material and preparing a low-refractive coating layer on the side of the phase difference layer away from the reflective linear polarizer through a coating process; the refractive index of the low-refractive coating layer is between the phase difference layer and air; Step 5: bonding the absorption type linear polarizer to the side of the reflection type linear polarizer away from the phase difference layer by adhesive and pressing them together to obtain a composite structure of absorption type linear polarizer-reflection type linear polarizer-phase difference layer; Step 6: Bond the side of the absorption linear polarizer away from the reflection linear polarizer to the lens glass through adhesive.
[0005] Preferably, the target material is one of amorphous silicon dioxide, a mixture of aluminum oxide and silicon dioxide, and molybdenum oxide; the coating process is one of vacuum evaporation coating, vacuum sputtering coating, vacuum ion coating, and vacuum chemical vapor deposition coating; When preparing the low-fold coating, the material to be coated is placed at a distance of 0.2-1m from the target material, and the coating is carried out in an environment with a vacuum degree of less than 30Pa, and the coating time is 30-300 seconds; The components of the adhesive include acrylate monomers, amino ester monomers, isocyanate curing agents, epoxy curing agents, free radical photoinitiators, ionic photoinitiators, silane coupling agents, and solvents. The adhesive is cured by heating or light curing, or a combination thereof.
[0006] Preferably, the refractive index of the low-refractive coating layer is 1.3-1.48.
[0007] Preferably, the dry film thickness of the low-reflection coating satisfies the following formula: λ = 4 × (1.58-n) × d / cosθ; Among them, λ is the designed central wavelength, n is the refractive index of the low-refractive coating material, d is the dry film thickness of the low-refractive coating, and θ is the refraction angle of light after it is incident from air to the low-refractive coating.
[0008] Preferably, in step one, the components of the photoalignment solution include azo compounds, cinnamoyl compounds, coumarin compounds, polyimide compounds, and solvents. The coating dry film thickness of the photoalignment solution is 10-300nm. After the photoalignment solution is coated, it is dried at a temperature of 0-150°C for 10-1000 seconds. During the drying process, the photoalignment solution is exposed to light with an exposure intensity of 5-500mJ and an exposure wavelength of 200-600nm.
[0009] Preferably, the alignment angle of the photo-alignment layer is adjusted by adjusting the relative angle between the polarization angle of the exposure light source and the reference edge of the photo-alignment layer to achieve adjustment of the slow axis angle of the phase difference layer; the alignment angle of the photo-alignment layer is set to form an angle of 45 degrees with the transmission axis of the reflective linear polarizer.
[0010] Preferably, in step 2, after the liquid crystal solution is uniformly coated on the alignment layer, it is irradiated with ultraviolet light in a nitrogen atmosphere and dried; The liquid crystal solution is composed of lyotropic or thermotropic liquid crystal molecules with reactive functional groups dissolved in a solvent, the solution concentration is 5-50%, the drying temperature is 40-150°C, the drying time is 10-1000 seconds, the ultraviolet light irradiation intensity is 5-500mJ, and the ultraviolet light wavelength is 200-400nm; under 550nm wavelength light, the in-plane delay of the phase difference layer is 115-155nm, the transmittance of the phase difference layer is ≥90%, and the haze of the phase difference layer is ≤1%.
[0011] Preferably, the liquid crystal solution and the photo-alignment solution are coated by one of micro-concave coating, slit coating and extrusion bar coating.
[0012] A circular polarizing composite film comprises a low-refractive coating, a phase difference layer, a reflective linear polarizer, an absorbing linear polarizer and lens glass in sequence.
[0013] The beneficial effects of the present invention are: 1. The present invention replaces the traditional phase difference film prepared by stretching a polymer film material with a phase difference layer made of liquid crystal material. The phase difference layer made of liquid crystal material can be prepared by coating a liquid crystal solution, which can greatly reduce the thickness of the phase difference film, thereby reducing the phase difference between the upper and lower surfaces of the phase difference film, thereby alleviating the image ghosting problem; and thanks to the reduction in the thickness of the phase difference film, the overall thickness of the circularly polarized composite film can be significantly reduced, making the entire optical device thinner and lighter, and the bendability is also significantly improved.
[0014] 2. In the present invention, a phase difference layer is prepared by optical alignment of a liquid crystal solution. The phase difference layer can be oriented obliquely during the preparation process. Oblique alignment means that the liquid crystal molecules are not arranged completely parallel to the substrate surface, but have a certain tilt angle. This alignment method can give the phase difference layer unique optical properties, such as wide viewing angle, high transparency, etc. The flexibility of oblique alignment makes it possible to adjust the alignment angle according to different application needs to meet specific optical requirements. Since the alignment angle is relatively flexible, it can adapt to the roll-to-roll production process. The roll-to-roll production process is efficient and flexible, which can effectively improve production efficiency, and has a high cutting utilization rate, reducing material waste.
[0015] 3. The present invention provides a low-refractive coating on one side of the phase difference film. After the low-refractive coating is added, when light is incident from the air layer through the low-refractive coating to the surface of the phase difference layer, it will be reflected at the side of the low-refractive coating in contact with the air and the side of the low-refractive coating in contact with the phase difference layer. When the optical path difference of the two reflected light beams is (2N+1)π (N is a natural number), they are superimposed and destructive. The present invention controls the thickness and refractive index of the low-refractive coating and utilizes the superposition and destructive effect of light to reduce or eliminate the surface reflection of the phase difference layer, thereby reducing or eliminating the problems of ghosting and interference color fringes.
[0016] 4. The present invention prepares the phase difference layer by coating the liquid crystal solution on the photo-alignment layer. The entire preparation process is non-contact production, and the appearance quality is better. However, the traditional polymer film stretching preparation process may cause defects on the film surface, such as wrinkles and scratches, due to contact and tension during the stretching process, thereby affecting the appearance quality of the product, and the appearance quality is not as good as the present invention.
[0017] 5. The present invention prepares a low-refractive coating layer on the phase difference layer based on a dry method (coating process). The coating process can obtain a very thin and uniform film, and its thickness and composition are highly controllable. The low-refractive layer obtained by the coating process has a low impurity content and high material stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a schematic structural diagram of the circularly polarized composite film of the present invention.
[0019] Figure 2 Schematic diagram of the return light path in the existing OLED display.
[0020] Figure 3 Schematic diagram of ghosting of an image.
[0021] Figure 4 Schematic diagram of the interference pattern generated for the image. DETAILED DESCRIPTION
[0022] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0023] Those skilled in the art should understand that, in the disclosure of the present invention, the terms "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the drawings, which are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the above terms should not be understood as limiting the present invention.
[0024] It is to be understood that the term "one" should be understood as "at least one" or "one or more", that is, in one embodiment, the number of an element may be one, while in another embodiment, the number of the element may be multiple, and the term "one" should not be understood as a limitation on the quantity.
[0025] like Figure 1 As shown, an OLED display device includes a circular polarizing composite film, wherein the circular polarizing composite film includes a low-refractive coating, a phase difference layer, a reflective linear polarizer, an absorbing linear polarizer, and a lens glass in sequence; The dry process preparation method of the circularly polarized composite film comprises the following specific steps: Step 1: uniformly coating the photo-alignment solution on the carrier layer to form a photo-alignment layer; Step 2: uniformly coating the liquid crystal solution on the photo-alignment layer and aligning the photo-alignment layer to obtain a phase difference layer, wherein the dry film thickness of the phase difference layer is 0.5-5 microns; and then separating the alignment layer from the phase difference layer; Step 3: coating an adhesive on the phase difference layer, placing a reflective linear polarizer on the phase difference layer and pressing the reflective linear polarizer on the phase difference layer to obtain a reflective linear polarizer-phase difference layer composite structure; Step 4: Using a low-refractive material as a target material and preparing a low-refractive coating layer on the side of the phase difference layer away from the reflective linear polarizer through a coating process; the refractive index of the low-refractive coating layer is between the phase difference layer and air; Step 5: bonding the absorption type linear polarizer to the side of the reflection type linear polarizer away from the phase difference layer by adhesive and pressing them together to obtain a composite structure of absorption type linear polarizer-reflection type linear polarizer-phase difference layer; Step 6: Bond the side of the absorption linear polarizer away from the reflection linear polarizer to the lens glass through adhesive.
[0026] In the present invention, a phase difference layer made of liquid crystal material replaces the phase difference film prepared by stretching a traditional polymer film material. The phase difference layer made of liquid crystal material can be prepared by coating a liquid crystal solution, which can greatly reduce the thickness of the phase difference film, and the thickness can reach 0.5-5 microns. The thickness of the traditional phase difference film prepared by stretching a polymer film material is generally greater than 50 microns. Since the thickness of the phase difference film in the present invention is greatly reduced, the phase difference between the upper and lower surfaces of the phase difference film is reduced, thereby alleviating the image ghosting problem; and thanks to the reduction in the thickness of the phase difference film, the overall thickness of the circularly polarized composite structure can be significantly reduced, making the entire optical device thinner and lighter, and the bendability is also significantly improved.
[0027] The present invention prepares the phase difference layer by photo-alignment of the liquid crystal solution. The phase difference layer can be obliquely aligned during the preparation process. Oblique alignment means that the liquid crystal molecules are not arranged completely parallel to the substrate surface, but have a certain tilt angle. This alignment method can give the phase difference layer unique optical properties, such as wide viewing angle, high transparency, etc. The flexibility of oblique alignment allows the alignment angle to be adjusted according to different application requirements to meet specific optical requirements; since the alignment angle is relatively flexible, it can be adapted to the roll-to-roll production process. The roll-to-roll production process has the characteristics of high efficiency and flexibility, which can effectively improve production efficiency, and has a high cutting utilization rate and reduces material waste. In addition, the present invention prepares the phase difference layer by coating the liquid crystal solution on the photo-alignment layer. The entire preparation process is non-contact production, and the appearance quality is better. However, the traditional polymer film stretching preparation process may cause defects on the surface of the film material, such as wrinkles, scratches, etc., due to contact and tension during the stretching process, thereby affecting the appearance quality of the product, and the appearance quality is not as good as the present invention.
[0028] When light is incident from the air layer to the surface of the material, the light is reflected due to the difference in refractive index of the materials on both sides of the incident interface. When the thickness between the two interfaces reaches the micrometer level or below, the reflected light from the two different interfaces interferes, thereby generating ghost images and interference fringes. The refractive index of the low-refractive coating layer is bounded by the material layer between the phase difference layer and the air layer. After the low-refractive coating layer is added, when the light is incident from the air layer through the low-refractive coating layer to the surface of the phase difference layer, it will be reflected on the side of the low-refractive coating layer in contact with the air and the side of the low-refractive coating layer in contact with the phase difference layer. When the optical path difference of the two beams of reflected light is (2N+1)π (N is a natural number), they are superimposed and destructive. When the optical path difference of the two beams of light is 2Nπ (N is a natural number), they are superimposed and additive. The present invention controls the thickness and refractive index of the low-refractive coating layer, and utilizes the superimposed and destructive effect of light to reduce or eliminate the surface reflection of the phase difference layer, thereby reducing or eliminating the ghost image and interference color fringes.
[0029] In the present invention, a low-refractive material is used as a target material and a low-refractive coating layer is prepared on the phase difference layer through a coating process (i.e., a dry process). The process has high precision and can prepare a coating with an extremely thin thickness. Moreover, the process is implemented in a closed negative pressure chamber, without solvent volatilization, and has little impact on the environment.
[0030] Among them, in step three, the absorption type linear polarizer and the phase difference layer are pressed together by a composite roller; on the one hand, the composite roller can apply pressure to the absorption type linear polarizer and the phase difference layer to ensure effective combination between the two, and on the other hand, the thickness of the adhesive between the absorption type linear polarizer and the phase difference layer can be controlled by the composite roller, thereby reducing the interference lines generated in the return light path.
[0031] Similarly, in step five, the absorptive linear polarizer and the reflective linear polarizer are pressed together by a composite roller; on the one hand, the composite roller can apply pressure to the absorptive linear polarizer and the reflective linear polarizer to ensure effective combination between the two, and on the other hand, the composite roller can control the thickness of the adhesive between the absorptive linear polarizer and the reflective linear polarizer, thereby reducing the interference patterns generated in the return light path.
[0032] In step 1, the components of the photo-alignment solution include azo compounds, cinnamoyl compounds, coumarin compounds, polyimide compounds, and solvents. The thickness of the dry film of the photo-alignment solution is 10-300 nm. After the photo-alignment solution is coated, it is dried at a temperature of 0-150° C. for 10-1000 seconds. During the drying process, the photo-alignment solution is exposed to light with an exposure intensity of 5-500 mJ and an exposure wavelength of 200-600 nm. The concentration of the photo-alignment solution is 1-5%.
[0033] The alignment angle of the photo-alignment layer is adjusted by adjusting the relative angle between the polarization angle of the exposure light source and the reference edge of the photo-alignment layer to adjust the slow axis angle of the phase difference layer; the alignment angle of the photo-alignment layer is set to form a 45-degree angle with the transmission axis of the reflective linear polarizer.
[0034] The alignment angle of the photo-alignment layer determines the arrangement direction of the liquid crystal molecules, and thus determines the slow axis angle of the phase difference film. By setting the alignment angle to be 45 degrees with the light transmission axis of the reflective linear polarizer, roll-to-roll lamination can be facilitated, the process complexity can be simplified, and the operation efficiency and material utilization can be improved.
[0035] In step 2, after the liquid crystal solution is uniformly coated on the alignment layer, it is irradiated with ultraviolet light in a nitrogen atmosphere and dried. The liquid crystal solution is composed of lyotropic or thermotropic liquid crystal molecules with reactive functional groups dissolved in a solvent, the solution concentration is 5-50%, the drying temperature is 40-150°C, the drying time is 10-1000 seconds, the ultraviolet light irradiation intensity is 5-500mJ, and the ultraviolet light wavelength is 200-400nm; the in-plane delay of the phase difference layer under 550nm wavelength light is 115-155nm, the transmittance of the phase difference layer is ≥90%, and the haze of the phase difference layer is ≤1%.
[0036] In this embodiment, the liquid crystal solution is composed of lyotropic or thermotropic liquid crystal molecules with reactive functional groups of carbon-carbon double bonds dissolved in a solvent, and the concentration of the liquid crystal solution is 5-50%. In the present invention, the transmittance of the phase difference layer is 90%, and the haze of the phase difference layer is less than 1%, which can effectively reduce the loss of light passing through the phase difference layer, and the user can obtain a higher quality image.
[0037] The coating method of the liquid crystal solution and the photo-alignment solution is one of micro-concave coating, slit coating and extrusion doctor bar coating.
[0038] In step 4, the target material may be amorphous silicon dioxide, a mixture of aluminum oxide and silicon dioxide, or molybdenum oxide. The coating process may be vacuum evaporation coating, vacuum sputtering coating, vacuum ion coating, or vacuum chemical vapor deposition coating.
[0039] When preparing the low-fold coating, the material to be coated is placed at a distance of 0.2-1m from the target material, and the coating is performed in an environment with a vacuum degree of less than 30Pa, and the coating time is 30-300 seconds.
[0040] The present invention prepares a low-refractive coating on the phase difference layer based on a dry method (coating process). The coating process can obtain a very thin and uniform film, and its thickness and composition are highly controllable. The impurity content in the low-refractive layer obtained by the coating process is small, and the material stability is high. During the coating process of the present invention, the target material is selected from amorphous silicon dioxide, a mixture of aluminum oxide and silicon dioxide, and molybdenum oxide. The above materials have high hardness, wear resistance and corrosion resistance. After the low-refractive coating is formed on the surface of the phase difference layer by the above materials, the low-refractive coating can be effectively prevented from being worn and corroded, and the stability of the low-refractive coating is ensured.
[0041] The refractive index of the low-refractive coating layer is between that of the phase difference layer and air. In this embodiment, the refractive index of the phase difference layer is about 1.6, and the refractive index of the low-refractive coating layer is 1.3-1.48.
[0042] The dry film thickness of the low-reflection coating satisfies the following formula: λ = 4 × (1.58-n) × d / cosθ; Wherein, λ is the designed center wavelength. In the embodiment, the designed center wavelength λ is 550nm. n is the refractive index of the low-refractive coating material, d is the dry film thickness of the low-refractive coating, and θ is the refraction angle of light after it is incident from air to the low-refractive coating.
[0043] Taking silicon dioxide as an example, the refractive index n of silicon dioxide material is 1.47, and the refraction angle is 45°, then the dry film thickness d of the low-refractive coating is 66nm.
[0044] The adhesive used in the present invention comprises components of acrylate monomers, amino ester monomers, isocyanate curing agents, epoxy curing agents, free radical photoinitiators, ionic photoinitiators, silane coupling agents, and solvents. The adhesive is cured by heating or light curing, or a combination thereof.
[0045] A circularly polarized composite film is prepared by the dry process preparation method described above.
[0046] like Figure 1 As shown, the prepared circular polarization composite structure includes, from top to bottom, a low-refractive coating layer, a phase difference layer, a reflective linear polarizer, adhesive, an absorptive linear polarizer, adhesive, and a glass lens.
[0047] Several different preparation examples of circularly polarized composite structures are provided below: Example 1:
[0048] Example 2:
[0049] Example 3:
[0050] Example 4:
[0051] Example 5:
[0052] By comparing the above examples, it can be seen that by changing the phase difference layer to a liquid crystal material and adding a low-reflection layer, the problems of ghosting and interference color fringes are effectively solved.
[0053] The present invention is not limited to the above-mentioned optimal implementation mode. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that are the same or similar to those of the present application fall within the protection scope of the present invention.
Claims
1. An OLED display device, characterized in that: It includes a circular polarizing composite film, which includes a low-refractive coating, a phase difference layer, a reflective linear polarizer, an absorbing linear polarizer, and lens glass in sequence; The dry process preparation method of the circularly polarized composite film comprises the following specific steps: Step 1: uniformly coating the photo-alignment solution on the carrier layer to form a photo-alignment layer; Step 2: uniformly coating the liquid crystal solution on the photo-alignment layer and aligning the photo-alignment layer to obtain a phase difference layer, wherein the dry film thickness of the phase difference layer is 0.5-5 microns; and then separating the alignment layer from the phase difference layer; Step 3: coating an adhesive on the phase difference layer, placing a reflective linear polarizer on the phase difference layer and pressing the reflective linear polarizer on the phase difference layer to obtain a reflective linear polarizer-phase difference layer composite structure; Step 4: Using a low-refractive material as a target material and preparing a low-refractive coating layer on the side of the phase difference layer away from the reflective linear polarizer through a coating process; the refractive index of the low-refractive coating layer is between the phase difference layer and air; Step 5: bonding the absorption type linear polarizer to the side of the reflection type linear polarizer away from the phase difference layer by adhesive and pressing them together to obtain a composite structure of absorption type linear polarizer-reflection type linear polarizer-phase difference layer; Step 6: Bond the side of the absorption linear polarizer away from the reflection linear polarizer to the lens glass through adhesive.
2. An OLED display device according to claim 1, characterized in that: The target material is one of amorphous silicon dioxide, a mixture of aluminum oxide and silicon dioxide, and molybdenum oxide; the coating process is one of vacuum evaporation coating, vacuum sputtering coating, vacuum ion coating, and vacuum chemical vapor deposition coating; When preparing the low-fold coating, the material to be coated is placed at a distance of 0.2-1m from the target material, and the coating is carried out in an environment with a vacuum degree of less than 30Pa, and the coating time is 30-300 seconds; The components of the adhesive include acrylate monomers, amino ester monomers, isocyanate curing agents, epoxy curing agents, free radical photoinitiators, ionic photoinitiators, silane coupling agents, and solvents. The adhesive is cured by heating or light curing, or a combination thereof.
3. The OLED display device according to claim 1, characterized in that: The refractive index of the low-refractive coating layer is 1.3-1.
48.
4. The OLED display device according to claim 1, characterized in that: The dry film thickness of the low-reflection coating satisfies the following formula: λ = 4 × (1.58-n) × d / cosθ; Among them, λ is the designed central wavelength, n is the refractive index of the low-refractive coating material, d is the dry film thickness of the low-refractive coating, and θ is the refraction angle of light after it is incident from air to the low-refractive coating.
5. The OLED display device according to claim 1, characterized in that: In step one, the components of the photoalignment solution include azo compounds, cinnamoyl compounds, coumarin compounds, polyimide compounds, and solvents. The coating dry film thickness of the photoalignment solution is 10-300nm. After the photoalignment solution is coated, it is dried at a temperature of 0-150°C for 10-1000 seconds. During the drying process, the photoalignment solution is exposed to light with an exposure intensity of 5-500mJ and an exposure wavelength of 200-600nm.
6. The OLED display device according to claim 5, characterized in that: The alignment angle of the photo-alignment layer is adjusted by adjusting the relative angle between the polarization angle of the exposure light source and the reference edge of the photo-alignment layer to adjust the slow axis angle of the phase difference layer; the alignment angle of the photo-alignment layer is set to form a 45-degree angle with the transmission axis of the reflective linear polarizer.
7. The OLED display device according to claim 1, characterized in that: In step 2, after the liquid crystal solution is uniformly coated on the alignment layer, it is irradiated with ultraviolet light in a nitrogen atmosphere and dried; The liquid crystal solution is composed of lyotropic or thermotropic liquid crystal molecules with reactive functional groups dissolved in a solvent, the solution concentration is 5-50%, the drying temperature is 40-150°C, the drying time is 10-1000 seconds, the ultraviolet light irradiation intensity is 5-500mJ, and the ultraviolet light wavelength is 200-400nm; under 550nm wavelength light, the in-plane delay of the phase difference layer is 115-155nm, the transmittance of the phase difference layer is ≥90%, and the haze of the phase difference layer is ≤1%.
8. The OLED display device according to claim 1, characterized in that: The coating method of the liquid crystal solution and the photo-alignment solution is one of micro-concave coating, slit coating and extrusion doctor bar coating.
9. A circularly polarized composite film, characterized in that: It includes a low-refractive coating, a phase difference layer, a reflective linear polarizer, an absorbing linear polarizer, and lens glass in sequence.
Citation Information
Patent Citations
Light splitting assembly and augmented reality display device
CN116430504A
Optical plate capable of repeatedly utilizing optical alignment layer as well as preparation process and application of optical plate
CN118276359A
Circular polarizer and display device
CN220526028U
Flexible display foldable device with independent hinge structure
KR1020220125010A